Persepsi dan Motivasi Generasi Z dalam Membaya Zakat Secara Digital - Muhammad Arief; Muhammad Arkan; Dinda Amelia; Sabila Rahmadani; Deby Anora (CV. Cendekiawan Muda Sriwijaya, 2026)
The development of digital technology has transformed various aspects of society, including the way zakat payments are conducted through online platforms. Generation Z, as a generation that has grown up in the internet era, demonstrates a strong tendency to utilize digital services, including online zakat payments. This study aims to analyze the perceptions and motivations of Generation Z in paying zakat through digital platforms in Indonesia. The research employs a descriptive qualitative method using the Theory of Planned Behavior (TPB) proposed by Icek Ajzen as the analytical framework. Data were collected through in-depth interviews, observations, and documentation involving Generation Z informants who had previously used digital zakat services. Data analysis was conducted using the interactive model developed by Matthew B. Miles and A. Michael Huberman. The findings reveal that Generation Z holds positive perceptions of digital zakat services, considering them practical, efficient, flexible, and easily accessible via smartphones. Their motivation to use digital zakat services is influenced by religious awareness, social concern, social media exposure, and the growing culture of cashless transactions. Nevertheless, concerns regarding data security and platform transparency remain significant barriers to the adoption of digital zakat services.